Amyloidbildning av Parkinsonproteinet -synuklein i cell-liknande miljö, in vitro, med crowding agents dextran och PEG - Löfgren, Emil; Pernhed, David; Pernsved, Monica; Persson, Elin; Rehnberg, Nikita; Svensson, Cecilia (My University, 2021)
All over the world life expectancy is increasing which leads to a higher prevalence of neurodegenerative diseases such as Parkinson’s Disease. The disease is chronic and leads to slow degradation of cells in the nervous system of the brain. -synuclein is a well-studied protein which is likely involved in Parkinson’s Disease. The purpose of this project is to experimentally study the aggregation kinetics of - synuclein in regard to excluded volume effects. Different sizes and concentrations of two macromolecular crowding agents, dextran and PEG, are used to mimic the crowded cell environment. Crowded conditions and their effect on the formation of -synuclein amyloids and aggregetion kinetics, are studied through a Thioflavin T-aggregation assay. SDS-PAGE, circular dichroism spectroscopy and AFM are used to complement and validate the assay results. Higher concentrations of crowding agents generates faster aggregation of -synuclein compared to lower concentrations. However the aggregation does not always increase linearly with crowding. Certain crowding agents promote elongation while others promote alternative mechanisms such as primary or secondary nucleation. Several experiments verify the occurance of soft interactions between PEG and -synuclein. The -synuclein aggregation process is rather complex and dependent on several factors. Crowding promotes faster aggregation and morphology studies suggest the formation of amyloid fibrills. The results verify the effect of excluded volume but further research is required to determine which part of the aggregation process it primarily affects.